2016
DOI: 10.3390/molecules21060687
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New PEEK/HA Composites with 3D HA Network Fabricated by Extrusion Freeforming

Abstract: Addition of bioactive materials such as calcium phosphates or Bioglass, and incorporation of porosity into polyetheretherketone (PEEK) has been identified as an effective approach to improve bone-implant interfaces and osseointegration of PEEK-based devices. In this paper, a novel production technique based on the extrusion freeforming method is proposed that yields a bioactive PEEK/hydroxyapatite (PEEK/HA) composite with a unique configuration in which the bioactive phase (i.e., HA) distribution is computer-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 74 publications
0
47
1
Order By: Relevance
“…Both Fig 3 and Table 3 show that 0.5GO-PEEK demonstrated unprecedented toughness properties (127.20% greater absorption energy than pristine PEEK), far superior than any other GO containing PEEK composite systems reported so far. The toughness of 0.5GO-PEEK also exceeds many other PEEK composites reinforced with different filler materials such as HA [35], SiO2 [36] and glass fibers [37]. To investigate the fracture mechanisms of the GO-PEEK composites, the morphology of tensile fractured sample surface was analyzed, see The effects of nGO % on the crystallinity of GO-PEEK composites were studied by XRD (Fig 5a) and the intensity of the characteristic peak 2θ=18° for all samples were listed in Table 4.…”
Section: Fig 2amentioning
confidence: 91%
See 1 more Smart Citation
“…Both Fig 3 and Table 3 show that 0.5GO-PEEK demonstrated unprecedented toughness properties (127.20% greater absorption energy than pristine PEEK), far superior than any other GO containing PEEK composite systems reported so far. The toughness of 0.5GO-PEEK also exceeds many other PEEK composites reinforced with different filler materials such as HA [35], SiO2 [36] and glass fibers [37]. To investigate the fracture mechanisms of the GO-PEEK composites, the morphology of tensile fractured sample surface was analyzed, see The effects of nGO % on the crystallinity of GO-PEEK composites were studied by XRD (Fig 5a) and the intensity of the characteristic peak 2θ=18° for all samples were listed in Table 4.…”
Section: Fig 2amentioning
confidence: 91%
“…Under such condition, the fillers actually serve as stress concentration sites that facilitate the crack initiation and propagation, compromising the overall composite structural integrity and reduced the energy dissipation ability of the composites [41]. Since the G band of GO is at 1595cm -1 and that of the benzene ring is at 1600 cm -1 [35,47,48], it is hard to distinguish between the two. However, it is noteworthy that the intensity of the characteristic peak is the greatest for 0.5GO-PEEK, which may be due to GO resulting in stronger polarizability of the crystal field [49].…”
Section: Fig 2amentioning
confidence: 99%
“…Polyetheretherketone (PEEK), a semi-crystalline thermoplastic biopolymer, possesses great potential as a bone-repair material due to its superior mechanical properties, excellent temperature resistance and good processability [ 1 , 2 , 3 , 4 , 5 ]. Polyglycolicacid (PGA), a bioresorbable polymer, has proven to have remarkable qualities of biocompatibility and degradability [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results presented in the study showed that low-temperature extrusion 3D printed scaffold had uniformity of its microstructure after printing parameter optimization. Yang and Vaezi developed a lowcost production technology to 3D print scaffolds and compression moulds of bioactive PEEK/HA composites for bone tissue engineering [52,53,54]. Table 2 depicts the process and methods of the technique as it is applied to create a bioactive PEEK/HA composite for bone tissue engineering scaffolds [52].…”
Section: Ree-dimensional Printing (3dp)mentioning
confidence: 99%